Mapping the milk value chain in Fatick, Senegal - Ba, Koki; Cesaro, Jean-Daniel; Ferrari, Serena (2024)
The dairy value chain in Fatick is underdeveloped, despite the region's strong potential. Fatick is essentially an agropastoral region, with nearly 68% of households raising cattle and/or goats. The region is unique in that its population is essentially made up of pastoralist and agropastoralist households. According to estimates by the Direction de l'Elevage (DIREL), the region's potential in 2020 was estimated at more than 278,941 head of cattle and almost 431,273 head of goats (Ba, 2023). However, this potential is not being exploited to the full because of an often-restrictive production environment and organizational dysfunctions that the players in the value chain are struggling to resolve.